Differential diagnosis of auditory hallucinations in teenagers. Assessment and difficulties: Case report of a 13 year old patient. (13th April 2021) - Jordá, C. Pastor; Carroll, P.; Bender, D.; Tumuluru, R.
Abstract : Introduction: Learning from a case of a 13 year old patient with auditory hallucinations for 2 months, admitted to the hospital due to suicidal ideation. Her mother had been diagnosed with Lupus and OCD. Her mood had been low for several months, probable mild intellectual disability. Objectives: Learn how to assess auditory hallucinations and possible new onset psychotic symptoms in teenagers. Learn about different levels of care involved. Discuss differential diagnosis and future directions and treatment. Methods: Description of the case. Differential diagnosis: Obsessive compulsive disorder, Major depressive disorder with Psychotic features, schizophrenia spectrum disorder, epilepsy or other neurologic disease, autoimmune disease, post-traumatic stress disorder… Tests and consults conducted by Neurology team Psychopharmacology description. Results: Differential diagnosis: Obsessive compulsive disorder, Major depressive disorder with Psychotic features, schizophrenia spectrum disorder, epilepsy, autoimmune diseases like Lupus, post-traumatic stress disorder etc. Video EEG: normal. Brain MRI: normal Blood work unremarkable with positive ANA (titer 1:80). Work up, including lumbar puncture with autoimmune encephalitis and MS panels was negative. Psychopharmacology: Fluoxetine up to 40mg, and Aripiprazol up to 20mg without a good response. Possible sexual trauma was disclosed in a second hospitalization, months later. Conclusions: Recommendation of assessing new onset of psychotic symptoms in detail to get a good diagnosis. Psychotic symptoms in young teenagers may occur as part of different presentations and it is important to provide a good follow up of the patient in order to provide the most accurate treatment. Conflict of interest: Alicia Koplowitz Foundation